Aspectos constitucionales del arbitraje. Entrevista a José Daniel Amado - Monge Morales, Gonzalo J. (2015)
What is the nature of arbitration? In which sourcerelies its binding force? How does its relation with the Judicial Power must be comprehended? Whichis  the  role  the Constitutional  Court  shall  havetowards it? What is the importance of arbitrationin relation with domestic and foreign investments?In the present article, the author provides answers to the aforementioned questions.  In  that  line, he mentions recent pronouncements of the Constitutional Court regarding the matter, and gives us his opinion about controversial issues that may arise.